Zinc Recovery From Brass Flue Dust - Saridede, Muhlis Nezihi; Altuner, Serdar (SPRINGER INDIA, 2007)
Recovery of zinc or reuse of brass melting flue dust is an economic and environmental necessity. Brass flue dust contains both high content of zinc and other metals hence it is considered a hazardous waste and not suitable for landfill. Zinc recovery from brass flue dust is the main subject of thiS work. First brass flue dust was briquetted with coke in a cylindrical shape, and then the briquettes containing solid reductant were reduced in a tube furnace to recover the zinc content of the flue dust. Zinc in the brass flue dust is recovered by vaporizing in the heating/reducing chamber and condensing it in the cooling chamber of the furnace. Several parameters have been studied in order to improve the reducing properties of the briquettes and in order to raise the zinc content of condensed powder. These parameters include time, temperature and coke ratio. Results indicated that degree of zinc removal and zinc content in the condensed powder increased with increasing time and temperature. The optimum reducing conditions were found to be temperature of 1100 degrees C, reducing time of 90 minutes and excess carbon usage (twice of what is required stoichiometrically). The zinc content in the residue was as low as 1.85% after the processing. Condensed powder contained both zinc and zinc oxide.
Keywords: REDUCTION; ASH; Metallurgy & Metallurgical Engineering